Design of Contextual and Islamic Values-Based Mathematics E-Modules for Junior High School Students - Aliyah, Himatul; Rahmawati, Nur Indah; Asy'arie, Bima Fandi; Mariyana, Weni; Nuraqilah, Maisarah (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2025)
This research aims to (1) Understand the contextual-based mathematics learning process and current Islamic values. (2) Produce a contextually based Mathematics E-Module product design and Islamic values ​​in Class VIII SPLDV material carried out by the Batanghari Islamic Qurani Middle School. The type of research used is research and development (Research and Development) using the ADDIE model, which consists of 5 stages. The research subjects were 13 students in class VIII of SMP Islam Qurani Batanghari. Data collection techniques in this research used interviews, questionnaires, and documentation. The data obtained is the validity and practicality of the product. The results of this research identified that there is no innovation in the learning process in learning methods that only use general methods, namely lecture, discussion, demonstration, and memorization. Our teaching materials also include student worksheets (LKS) and teacher handbooks. Then, this study produced a product in the form of a contextually based Mathematics E-Module and Islamic values ​​, which received the predicate of validity with an average score of 91%, and practicality based on student response questionnaires with an average score of 87% with very practical criteria. Based on this study, it can be concluded that the Mathematics E-Module based on contextual and Islamic values ​​in SPLDV Class VIII material at Islamic Middle School Qurani Batanghari is suitable for use as teaching material in junior high schools.